Macroalgal forest vs sea urchin barren: Patterns of macro-zoobenthic diversity in a large-scale Mediterranean study. (July 2020) - Pinna, S.; Piazzi, L.; Ceccherelli, G.; Castelli, A.; Costa, G.; Curini-Galletti, M.; Gianguzza, P.; Langeneck, J.; Manconi, R.; Montefalcone, M.; Pipitone, C.; Rosso, A.; et al.
Abstract: The study aimed at contributing to the knowledge of alternative stable states by evaluating the differences of mobile and sessile macro-zoobenthic assemblages between sea urchin barrens and macroalgal forests in coastal Mediterranean systems considering a large spatial scale. Six sites (100 s km apart) were selected: Croatia, Montenegro, Sicily (Italy), Sardinia (Italy), Tuscany (Italy), and Balearic Islands (Spain). A total of 531 taxa, 404 mobile and 127 sessile macro-invertebrates were recorded. Overall, 496 and 201 taxa were found in macroalgal forests and in barrens, respectively. The results of this large-scale descriptive study have met the expectation of lower macrofauna complexity and diversity in barrens rather than in macroalgal forests, and have allowed estimating the differences in levels of diversity and the consistency of variability across Mediterranean sites. Some peculiar patterns in barrens, related to both abundance of specific taxa and to high values of beta diversity, have been evidenced. Highlights: Macro-zoobenthic assemblages of barrens and macroalgal forests were studied. Six sites were studied throughout the Mediterranean Sea. A total of 531 taxa, 404 mobile and 127 sessile macro-invertebrates were recorded. 496 and 201 taxa were found in macroalgal forests and in barrens, respectively. A lower macrofauna complexity and diversity were found in barrens.